2009
DOI: 10.1063/1.3099932
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer friction and attachment effects on energy dissipation in graphene nanoresonators

Abstract: Band gap and effective mass of multilayer BN/graphene/BN: van der Waals density functional approach

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 17 publications
2
47
0
Order By: Relevance
“…Graphene oxides combining with the excellent properties of neat graphene, rich surface functional groups and low cost, are expected to be promising nano-scale filler for the next generation of functional composite materials [14]. Until recently, tribological studies on graphene preliminarily focus on the microscopic study of the tribological properties [15][16][17][18][19][20][21], solid lubrication film and coating [22][23][24][25][26][27] and lubricant additive [28][29][30]. There is little information available about the discussion of friction and wear behavior of monolithic polymer nanocomposites reinforced by graphene [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Graphene oxides combining with the excellent properties of neat graphene, rich surface functional groups and low cost, are expected to be promising nano-scale filler for the next generation of functional composite materials [14]. Until recently, tribological studies on graphene preliminarily focus on the microscopic study of the tribological properties [15][16][17][18][19][20][21], solid lubrication film and coating [22][23][24][25][26][27] and lubricant additive [28][29][30]. There is little information available about the discussion of friction and wear behavior of monolithic polymer nanocomposites reinforced by graphene [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Kim and Park [273] also studied the Q-factors of multilayer graphene NEMS, including both intrinsic effects (friction between the graphene monolayers), and extrinsic effects, or the effects of clamping strength between the graphene NEMS and the substrate. Interestingly, it was found that the quality of the attachment between the graphene NEMS and substrate had a strong effect on the Q-factor, where weaker attachment forces between the graphene NEMS and the substrate led to lower Q-factors.…”
Section: Atomistic Models: Carbon Nanotube Resonators and Graphene Shmentioning
confidence: 99%
“…9,28,29 As stated earlier, the performance of nanoresonators for sensing and transportation applications strongly depends on their dynamic characteristics such as quality (Q)-factor. [37][38][39] The Q-factor reflects the energy dissipated for each vibrational cycle of the resonators, which can be affected by the external attachment energy loss, 40,41 intrinsic nonlinear scattering mechanisms, 42 the effective strain mechanism, 43 edge effects, 44,45 grain-boundary-mediated scattering losses, 46 and temperature scaling phenomenon. 47 Moreover, the structure of nanoresonators has a large surface-to-volume ratio, which causes a difference in the nature of chemical bonds on the surface.…”
mentioning
confidence: 99%